Comparative political economy and varieties of macroeconomics - Lucio Baccaro; Jonas Pontusson (Max Planck Institute for the Study of Societies, 2018)
This paper provides a historical overview of comparative political economy as an interdisciplinary field of study anchored in political science and focused on advanced capitalist states. We argue that this field of inquiry has reached an impasse and that a more sustained engagement with macroeconomics provides a way forward. Against this backdrop, we review two distinct traditions of macroeconomics - New Keynesian and Post-Keynesian macroeconomics - and discuss their relative merits as vehicles for renewing the research agenda of comparative political economy. – – Dieses Paper bietet einen historischen Überblick über die Vergleichende Politische Ökonomie als interdisziplinäres, in der Politikwissenschaft verankertes und auf die entwickelten kapitalistischen Länder bezogenes Forschungsfeld. Wir argumentieren, dass dieses Forschungsfeld in einer Sackgasse steckt und dass eine grundlegendere Auseinandersetzung mit der Makroökonomie nötig ist, um voranzukommen. Vor diesem Hintergrund wenden wir uns zwei unterschiedlichen Traditionen der Makroökonomie zu - dem Neokeynesianismus und dem Postkeynesianismus - und diskutieren, inwiefern diese als Instrumente zur Erneuerung der Forschungsagenda der Vergleichenden Politischen Ökonomie beitragen können.
hdl:21.11116/0000-0002-AF0D-C
Keywords: 300; comparative capitalisms; comparative political economy; growth models; macro-economics; varieties of capitalism; Makroökonomie; Spielarten des Kapitalismus; Vergleichende Kapitalismusforschung; Vergleichende Politische Ökonomie; Wachstumsmodelle